2009
DOI: 10.1074/jbc.m109.027912
|View full text |Cite
|
Sign up to set email alerts
|

Nα-Tosyl-l-phenylalanine Chloromethyl Ketone Induces Caspase-dependent Apoptosis in Transformed Human B Cell Lines with Transcriptional Down-regulation of Anti-apoptotic HS1-associated Protein X-1

Abstract: was originally synthesized as a specific inhibitor of chymotrypsin-like serine proteases (1) and has been widely used to investigate signal transduction pathways that are involved in gene expression and cell survival/cell death. However, contradictory effects of TPCK on apoptosis have been reported. Hence, TPCK was shown to prevent apoptosis in a cell death stimulus-dependent manner in some model systems (2-4), and a recent study also suggested that TPCK may diminish apoptosis by direct and nonspecific inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…Disruption of the mitochondrial membrane potential is known to induce release of cytochrome c from mitochondria into the cytosol, where cytochrome c leads to the generation of caspase-9 and activates downstream caspases, which ultimately induces the cell to undergo apoptosis [27]. In our experiment, a loss of ∆Ψm in 4T1 cells was also observed after YLT26 treatment.…”
Section: Discussionsupporting
confidence: 62%
“…Disruption of the mitochondrial membrane potential is known to induce release of cytochrome c from mitochondria into the cytosol, where cytochrome c leads to the generation of caspase-9 and activates downstream caspases, which ultimately induces the cell to undergo apoptosis [27]. In our experiment, a loss of ∆Ψm in 4T1 cells was also observed after YLT26 treatment.…”
Section: Discussionsupporting
confidence: 62%
“…Nevertheless, TPCK can also inhibit some cysteine proteases including at some extent even caspases [38,39]. Contrasting reports, in some cases from the same team, have shown that, depending on the cell type, dose and the nature of co-signals, TPCK may either partially inhibit caspase activation and activity or promote caspase activation and apoptosis [38][39][40][41][42]. Nevertheless, in our experimental conditions, the degradation of Puma induced by TRAIL or anisomycin in Jurkat or BL41 cells was prevented by adding TPCK to the medium, without inhibiting the activation (as assessed by monitoring the disappearance of the proform caspase) and activity (as assessed by monitoring cleavage of the caspase-3 substrate PARP-1) of caspase-3 in these cells.…”
Section: Discussionmentioning
confidence: 97%
“…Cell lysates were combined with the fluorogenic, caspase-3-specific substrate Ac-Asp-Glu-Val-Asp-7-amino-4-methylcoumarin (DEVD-AMC) in a standard reaction buffer (Jitkaew et al, 2009), and real-time measurements of enzyme-catalyzed release of AMC were obtained using a Tecan Infinite F200 plate reader (Tecan Group Ltd, Männedorf, Switzerland) operating with Magellan version 6.5 software (Tecan Group Ltd, Männedorf, Switzerland). Fluorescence values were converted to picomoles, and the maximum rate of AMC release (picomoles per minute) was estimated for each sample.…”
Section: Methodsmentioning
confidence: 99%
“…Loss of mitochondrial membrane potential was detected using tetramethylrhodamine ethyl ester (TMRE) (Molecular Probes, Eugene, OR) (Jitkaew et al, 2009). In brief, 20 minutes prior to harvesting the cells, 1 ml (TMRE 25 nM) was added to the cell cultures.…”
Section: Methodsmentioning
confidence: 99%